Effective Management and Its Impact on Growth of Small and Medium Sized Pakistani Firms - Jamil, Khalid; Zeeshan, Muhammad; Raza, Hamad (Information Management and Business Review, 2017)
The study is held to observe the impact of Management including Management levels and decision making on the growth of small firms. Study area is Punjab (Pakistan). Small firms have no proper firm structure; they do not follow the formal rules to run the organization. In spite of this, these firms are growing rapidly. If these firms have effective management levels and rational decision making than the firms will grow rapidly. The results show a significant increase in growth by using rational decision making and having effective management levels. Statistical results show that if we spend 1% on independent variable, then it shows an 80% increase in dependent variable.